The Influence of Abusive Supervision on Higher Educational Lecturer's Performance: The Mediating Role of Emotional Exhaustion and Innovative Work Behaviour - Sasmitha, Jonathan Lucky; Sobandi, A.; Suryadi, Edi; Rofaida, Rofi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
Leadership in education, particularly in secondary and higher education in Indonesia, plays a crucial role in shaping the performance, innovation, and sustainability of educators. However, abusive supervision practices are still prevalent and have the potential to negatively impact lecturer motivation and retention. This study explores the influence of Abusive Supervision (AS) by educational leaders on Lecturer Intention to Quit (LIQ), with Emotional Exhaustion (EE), Innovative Work Behavior (IWB), and Higher Education Lecturer Performance (HELP) as mediating variables. The study population consisted of lecturers working in private and public university in West Java, Indonesia. A total of 115 lecturers voluntarily participated in this study by completing a questionnaire based on a validated measurement scale. A quantitative approach with a survey design was used, and data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that AS significantly increased EE and LIQ, while decreasing IWB and HELP. Furthermore, IWB had a positive effect on HELP, while HELP had a negative relationship with LIQ. Mediation analysis confirmed that IWB and HELP mediated the relationship between AS and LIQ, while EE had no effect on HELP, thus not acting as a mediator. These findings confirm that abusive supervision has a detrimental impact on lecturer innovation, performance, and retention. This study concludes that abusive supervision has serious implications for the sustainability of higher education, making leadership style transformation an urgent need.